Governance and value creation in hybrid organisations: a comparative case study of Sistema B and B Corps in Brazil - Garcia, Maria Lucia Villela (2016)
B Corps is a growing contemporary phenomenon, attracting not only the media attention, but also entrepreneurs interested in developing organisations that set their purpose to “redefine success in business” and “use the power of business to solve social and environmental problems” (B Lab, 2012). By combining two different logics (i.e. social and economic), B Corps are regarded as hybrid organisations. Battilana and Lee (2014) have made a significant contribution to the literature on the hybrid organisation, by providing an ideal type that makes it easier to examine this kind of organisation. However, we claim that the literature on this topic should go beyond that ideal type and engage in the challenges and opportunities that surround hybrid organisations in daily life practices. The lack of studies on B Corps worldwide and mostly in Brazil presents the empirical gaps for our research to address. Additionally, the overlook of the governance role and concentration of studies in the hybridity tensions, within the institutional logics literature, provide us with two theoretical gaps. They are explored by giving governance its prominent role in enabling hybridity and bringing three other concepts to advance the literature of hybrid organisations, such as stakeholder engagement, value creation and business model. A comparative case study method is employed to analyse five organisations, four B Corps (i.e. Abramar, Avante, Combio and Via Gutenberg) and Sistema B Brazil. The analysis reveals that governance is pivotal in the creation of social, economic and ecological values contemplated in the organisation’s business model. Moreover, there is enough evidence to support that stakeholders’ participation and engagement is what enable governance to access those values in the business model. As a result, a new conceptualisation for hybrid organisations, in the context of B Corps, is proposed.